EXECUTION OF FIDUCIARY COLLATERAL POST CONSTITUTIONAL COURT DECISION NUMBER 18/PUU-XVII/2019 IN SHARIA FINANCING SAVING AND LOAN COOPERATIVES BAITUL MAL WA TAMWIL - Arief Rahman; Danang Wahyu Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research is included in the type of normative juridical legal research. Empirical juridical research is a type of research that uses and processes facts such as books, journals, and other literacies such as interviews and real behavior obtained by direct observation. Fiduciary as collateral is one of the elements in a process of financing, credit and receivables. In this process, there is first a subject or parties involved in a consumer financing legal relationship. Second, there are objects or everything the consumer needs that will be agreed upon. Furthermore, the agreement itself contains clauses and articles that are agreed, of course, with everything that is agreed upon by both parties along with all rights and obligations. Finally, there is a guarantee that will be used in the engagementTo obtain this research material, the researcher uses the literature study method, namely by studying legal materials and with field studies that examine the facts in the field